2020
DOI: 10.1038/s41598-020-62980-2
|View full text |Cite
|
Sign up to set email alerts
|

Gamma3 nail with U-Blade (RC) lag screw is effective with better surgical outcomes in trochanteric hip fractures

Abstract: The objective of this retrospective study was to investigate the surgical outcomes of AO/OTA 31 A1-3 trochanteric fractures treated with the new-generation Gamma3 nail with U-Blade (RC) lag screw and to analyze the risk factors related to fixation failure. A total of 318 consecutive patients who underwent cephalomedullary nailing using Gamma3 nail with U-Blade lag screw for trochanteric hip fractures between September 2015 and June 2018 were enrolled. The average age was 80 years and most patients (69%) were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The presence of a BCF was the most significant risk factor for postoperative screw cut-out, regardless of the fixation device used. Several studies have recently reported favorable clinical results using improved nail designs, such as a rotationcontrolled lag screw with a U-clip, a helical blade, and twin interlocking derotation and compression screws [15,[25][26][27]. Large-scale randomized prospective studies are…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a BCF was the most significant risk factor for postoperative screw cut-out, regardless of the fixation device used. Several studies have recently reported favorable clinical results using improved nail designs, such as a rotationcontrolled lag screw with a U-clip, a helical blade, and twin interlocking derotation and compression screws [15,[25][26][27]. Large-scale randomized prospective studies are…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition to the continuous improvements in implant design to enhance fixation stability, short CMNs have showed favourable outcomes for the aforementioned fractures. 4…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition to the continuous improvements in implant design to enhance fixation stability, short CMNs have showed favourable outcomes for the aforementioned fractures. 4 As the ageing population increases, the number of elderly patients who suffer unstable pertrochanteric fractures with marked osteoporosis and the corresponding risk of fixation failure in this population increases. 5 In osteoporotic elderly patients, the medullary canal diameter widens, whereas the cortex becomes thinner, 6 and the variety of usable short CMN diameters is limited in practical terms due to stock issues (although this may be slightly different for each manufacturer).…”
Section: Introductionmentioning
confidence: 99%
“…Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license ( http://creativecommons.org/licenses/by-nc-nd/4.0/ ) associated with comminution of the posterior cortex, are known to be at high risk of fixation failure, including implant cut-out [3] . Therapy failure is mainly caused by varus collapse of the femoral head fragment and/or implant cut-out [4] .…”
Section: Introductionmentioning
confidence: 99%